A native bird as a predator for the invasive apple snail, a novel rice field invader in Europe. Issue 5 (11th June 2018) - Bertolero, Albert; Navarro, Joan
Abstract: Since 2009 the apple snail Pomacea maculata has become a new invader of Oryza sativa (rice) fields and wetlands in Europe, only invading the Ebro Delta (north‐eastern Spain) thus far. It is considered a highly invasive and damaging species, resulting in large economic losses worldwide. Despite the severe impact of the invasive apple snail on both cultivated and natural wetlands, it has become an abundant potential resource for native avian predators. In this study, stable isotope analysis was used to assess the consumption of the apple snail by the glossy ibis Plegadis falcinellus in the Ebro Delta. The results indicate the importance of the apple snail in the diet of this native bird. In particular, isotopic results indicated that apple snails and freshwater coleopterans were the main prey in the diet of glossy ibis chicks, accounting for 26–40% of their diet. Thus, this native bird species could potentially help in the biological control of this invasive snail, but is not expected to eradicate it. Although the spread of this pest in rice fields and wetlands is not desirable, we predict that the apple snail will follow a path similar to other invasive species, such as the red swamp crayfish Procambarus clarkii, in establishing itself as part of the wetland food web.